Food and development - Young, E. M (New York Routledge, 2012)
"The relationship between food and development has always been controversial. Over the last 30 years, development in the north and south has failed to deliver people a decent diet. While some people have too little food and die as a consequence; some people have too much food and die from associated diseases. Furthermore, some methods of food production create social dislocation and deadly environments where biodiversity is eroded and pollution is rampant. While guaranteeing enough food for the world?s inhabitants continues to be a serious challenge, new issues about food have emerged. Food and Development is a lively and lucidly written text which provides a clear and accessible introduction to these complex and diverse food related problems. It explores the continued prevalence of mass under nutrition in the developing world; acute food crises in some places associated with conflict; the emergence of over nutrition in the developing world and the vulnerability of the contemporary global food production system. The text identifies the major problems and analyses factors at the international, national and local scales to understand their continued prevalence. The book concludes by evaluating the potential of some oppositional forces to challenge the hegemony of the contemporary food system"
Includes bibliographical references (p. [387]-402) and index
Keywords: Food supply